Pinpoint size port d’Entrée as a predictor for better clinical outcome in pediatric endophthalmitis: A case series (Indian Journal of Case Reports, 2022)
Endophthalmitis is an intraocular inflammation involving both posterior and anterior segments, caused by bacterial or fungal infections. Here, we present a case series of five cases presented to the National Referral Hospital from January to December 2017. Five eyes were identified, including exogenous and endogenous odontogenic causes. All eyes were managed with vitrectomy, intravitreal antibiotics, and systemic antibiotics. Documented final best VA were 20/40 (20%), 1/300 (40%), and no light perception with phthisis bulbi (40%). Despite aggressive timely treatments, visual prognosis are poor in both endogenous and exogenous endophthalmitis. The best final VA 6/12 was found in the smallest port d’entrée size (pinpoint). Other characteristics did not show any significant clinical difference. Pinpoint size or smaller port d’entrée suggests better visual outcomes in pediatric endophthalmitis.